2020
DOI: 10.1007/s12250-020-00325-z
|View full text |Cite
|
Sign up to set email alerts
|

Beta- and Novel Delta-Coronaviruses Are Identified from Wild Animals in the Qinghai-Tibetan Plateau, China

Abstract: Outbreaks of severe virus infections with the potential to cause global pandemics are increasingly concerning. One type of those commonly emerging and re-emerging pathogens are coronaviruses (SARS-CoV, MERS-CoV and SARS-CoV-2). Wild animals are hosts of different coronaviruses with the potential risk of cross-species transmission. However, little is known about the reservoir and host of coronaviruses in wild animals in Qinghai Province, where has the greatest biodiversity among the world's high-altitude region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Moreover, broad phenotypic alterations and potential dysfunctions were still prominent in those T cells in individuals clinically recovered from COVID-19 (Yang et al . 2020a , b ). It is still unknown, after being recovered for a long time, whether the altered non-specific T cell responses could bounce back and whether the specific T cell responses are sustainable.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, broad phenotypic alterations and potential dysfunctions were still prominent in those T cells in individuals clinically recovered from COVID-19 (Yang et al . 2020a , b ). It is still unknown, after being recovered for a long time, whether the altered non-specific T cell responses could bounce back and whether the specific T cell responses are sustainable.…”
Section: Introductionmentioning
confidence: 97%
“…The mutations of viruses are common and, as a consequence, the SARS-CoV-2 can acquire mutations with fitness advantages and immunological resistance [1,25]. Several researchers have devoted time to study evolutionary transitions in order to ensure effectiveness of the vaccines and immunotherapeutic interventions [1,[26][27][28][29]. A new variant of the SARS-CoV-2 virus has been detected in England, and is the VOC-202012/01 of lineage B.1.1.7.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the SARS-CoV-2 is mutating, and its transmission is more efficient [26,[73][74][75]. There is a growing literature about new variants of the SARS-CoV-2, but it is, of course, not clear what further variants will occur in the future [1,[26][27][28][29]. For instance, using analysis of the frequency of the 614D and 614G variants, over time, it has been suggested that locations that reported 614D viruses early in the pandemic were often later dominated by 614G viruses [1].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding mutations, SARS-CoV-2 could acquire mutations with fitness advantages and immunological resistance [71]. Therefore, studying evolutionary transitions is important to ensure effectiveness of the vaccines and immunotherapeutic interventions [151, 50, 104, 157, 71]. It has been stateded that not only is the efficacy of the vaccine important, but whether a vaccine reduces infection and transmission as well as disease progression [69].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that the SARS-CoV-2 is mutating and its transmission is more efficient [151, 98, 33, 77]. There is a growing literature about mutations of the SARS-CoV-2, but it is not clear what further mutations could occur in the near future [151, 50, 104, 157, 71].…”
Section: Introductionmentioning
confidence: 99%